Crystallization and preliminary X-ray crystallographic analysis of human phosphodiesterase 12 - Kohno, Tetsuya (International Union of Crystallography, 2010)
Phosphodiesterase PDE12 is a medically important esterase-family member that hydrolyzes 2′–5′-linked oligoadenylates (2-5A), which are involved in the regulation of biological processes related to the antiviral and antitumour activity that can be induced by interferons. Here, cloning, purification and crystallization of the C-terminal endonuclease/exonuclease/phosphatase-homology domain of human PDE12 is reported. The crystals belonged to space group P3(1)21 or P3(2)21, with unit-cell parameters a = b = 111.3, c = 192.4 Å, and diffracted to 2.5 Å resolution. Assuming the presence of three molecules in the asymmetric unit, the solvent content was estimated to be about 44.0%.